The Main Aspects of End-to-End Standardisation of Herbal Drugs, Herbal Drug Preparations, and Herbal Medicinal Products of Eucalyptus viminalis - I. N. Zilfikarov; J. V. Daironas; I. I. Bochkareva; B. G. Bochkarev (Регуляторные исследования и экспертиза лекарственных средств, 2022)
The principle of consistent, end-to-end standardisation builds upon the fact that qualitative and quantitative analysis of bioactive compounds in herbal drugs, herbal drug preparations, and corresponding herbal medicinal products involves the same methods of analysis. The possibility of such standardisation should be considered at the stage of specification development. The aim of the study was to explore approaches to analysing of Eucalyptus viminalis leaves and chlorophyllipt medicinal products, observing the principle of end-to-end standardisation. Materials and methods: the authors analysed Eucalyptus viminalis as a herbal drug (leaves), a herbal drug preparation (chlorophyllipt soft extract), and herbal medicinal products (Chlorophyllipt®, 1% alcohol solution for oral, cutaneous, rectal, and vaginal use; 2% oil solution for cutaneous and vaginal use; and 25 mg orodispersible tablets) by direct UV spectrophotometry, thin-layer chromatography (TLC), and qualitative reactions. Results: the study demonstrated the possibility of using a herbal reference standard of eucalimin to analyse the Eucalyptus viminalis herbal drug and chlorophyllipt preparations and medicinal products in different dosage forms by TLC. Conclusions: procedures for determination of total phenolic aldehydes, if included into specifications and production technology of chlorophyllipt preparations and products, ensure compliance with the principle of end-to-end standardisation and allow for quantitative determination and control of active ingredients throughout the product lifecycle: from the acceptance of raw materials, through in-process controls, to testing and monitoring of finished products’ quality.